“Efecto de tres niveles de área foliar y cuatro dosis de ácido indolbutírico en el enraizamiento de amahua (plukenetia polyadenia muell.arg.), en San Martín” - Diaz Estela, Gonzalo (2009)
In the present work, the effects of three levels of leaf area and four doses of acid-3-indole-butyric (AIB) on the rooting capacity of juvenile cuttings of amahua (Plukenetia polyadenia Muell Arg.) Were evaluated using chambers of subirrigation. The trial was carried out in the nursery of the Institute of Investigations of the Peruvian Amazon in San Martín (llAP); Using a completely randomized design with a factorial arrangement consisting of twelve treatments, three replicates and four stakes per experimental unit. At the end of 20 days a 100% rooting was obtained on cuttings with 26 cm2 of leaf area and 0.6% of IBA. It is necessary, the use of shade on propagators to reduce irradiation, air temperatures and relative humidity